Pelatihan Metode Pemasaran Melalui Pembentukan Koperasi pada Pelaku Usahatani Sayuran Hidroponik di Kawasan Ekowisata Pulau Kemaro Kota Palembang - Muhammad Arbi; Sriati; Yulian Junaidi; M. Yamin; Gatot Priyanto (I-Com: Indonesian Community Journal, 2025)
This training aims to introduce, train and assist hydroponic vegetable farmers who live in the Kemaro Island Ecotourism Area RT 17 and 18, I Ilir Village, Ilir Timur II District, Palembang City. The activity was carried out by delivering material and practicing the formation of cooperatives to 30 participants. Pre-tests and post-tests were carried out to evaluate the activity. The results of the activity showed that the residents of Kemaro Island were very enthusiastic about immediately having a business entity in the form of a cooperative. It's just that they are not yet fully convinced because most of them have never been members of a cooperative. In addition, it is known that many residents have side businesses such as fish crackers, kempelang, food stalls, sweet stalls, street vendors, tire repairs, hairdressers, and many more businesses, both side businesses and as main jobs. With the training, it is hoped that the cooperatives that will be formed later can provide additional capital to business actors so that this has the potential for the growth of cooperatives in the midst of small communities.